IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DENGAN METODE HIRADC DI PT. INTI GANDA PERDANA (STUDI KASUS DEPARTEMEN PRODUKSI) - Ardyanto, Slamet; Indriastiningsih, Erna; Nugrahadi, Bekti (JURNAL ILMIAH EDUNOMIKA, 2025)
Occupational Health and Safety (OHS) is a crucial aspect of manufacturing industry operations, particularly in activities involving interactions between humans, machines, and materials. This study aims to identify, evaluate, and classify potential hazards and the associated risk levels in various work processes, including Picking Differential Carrier, Small Part Preparation, Brake Assembly & Retainer Press, Axle Shaft & Brake Install, and Nut Brake Tightening. The analysis method employs a systematic approach to different types of hazards—chemical, physical, mechanical, and ergonomic—followed by an assessment of probability and impact levels. The results indicate that most hazards fall within the "unlikely" to "possible" probability categories, with risk levels ranging from low to moderate. The dominant hazards identified stem from mechanical factors, such as the risk of being struck or scratched by materials, and ergonomic factors related to non-ergonomic working postures. Implemented controls include the use of personal protective equipment (PPE), enforcement of work instructions, installation of visual warning systems, and technical modifications to machinery. It can be concluded that risk management has been conducted effectively; however, continuous evaluation is necessary to ensure a safe, healthy, and productive working environment for employees. Keywords: Effectiveness, HIRADC, Implementation, Manufacture, OHS.